2013
DOI: 10.1186/1472-6815-13-10
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial isolates and drug susceptibility patterns of ear discharge from patients with ear infection at Gondar University Hospital, Northwest Ethiopia

Abstract: BackgroundEar infection is a common problem for both children and adults especially in developing countries. However in Ethiopia particularly in the study area, there is no recent data that shows the magnitude of the problem. The aim of this study was to determine the bacterial isolates and their drug susceptibility patterns from patients who had ear infection.MethodA retrospective study was conducted from September, 2009 to August, 2012 at Gondar University Hospital, Northwest Ethiopia. Ear discharge samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
63
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(112 citation statements)
references
References 14 publications
38
63
10
1
Order By: Relevance
“…The finding of Proteus mirabilis as the most common isolate is similar to findings by Chirwa in 2014 in Malawi where Proteus mirabilis accounted for 28.6%, 12 Aduba et al in 2010inGarissa (Kenya) where Proteus mirabilis accounted for 32.7%, 16 and Muluye et alin 2013 in Ethiopia were Proteus mirabilis accounted for 27.5%. 17 These findings are different from those of other studies where they found that pseudomonas aeruginosa was the most common isolate. 1,5,18 The difference in the pattern of microbiological isolates may be explained by differences in the geographical conditions and population dynamics.…”
Section: Discussioncontrasting
confidence: 71%
“…The finding of Proteus mirabilis as the most common isolate is similar to findings by Chirwa in 2014 in Malawi where Proteus mirabilis accounted for 28.6%, 12 Aduba et al in 2010inGarissa (Kenya) where Proteus mirabilis accounted for 32.7%, 16 and Muluye et alin 2013 in Ethiopia were Proteus mirabilis accounted for 27.5%. 17 These findings are different from those of other studies where they found that pseudomonas aeruginosa was the most common isolate. 1,5,18 The difference in the pattern of microbiological isolates may be explained by differences in the geographical conditions and population dynamics.…”
Section: Discussioncontrasting
confidence: 71%
“…Al-Azawy et al (2015) reported that rate isolate of ears P. mirabilis was 7% and rate isolate of urinary P. mirabilis was 24.24% [24]. Muluye et al (2013) reported that predominant proteus species in ear infections was 27.5% [26]. Mordi and Momoh (2009) mentioned that wounds P. mirabilis accounts 17.5% [27].…”
Section: Prevalence Of Proteus Mirabilismentioning
confidence: 99%
“…The extract was aseptically streaked on sterilized nutrient agar plates and incubated at 37°C for 24h for sterility check. The extracts that showed no growth was reconstituted by dissolving in 5% Dimethylsulphoside (DMSO) to obtain 200, 100, 50, 25…”
Section: The Percentage Extract Yield Was Estimated As= (Dry Weight Xmentioning
confidence: 99%